1999
DOI: 10.1002/(sici)1096-8628(19991029)86:5<492::aid-ajmg17>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

M�bius sequence, hypogenitalism, cerebral, and skeletal malformations in two brothers

Abstract: Two brothers born to a healthy, consanguineous Spanish couple have a syndrome of Möbius sequence with involvement of cranial nerves V, VI, VII, IX, and XII, central nervous system malformations; characteristic face with creased earlobes, short philthrum, and a short, arched upper lip, skeletal anomalies with short sternum and delayed bone maturation, hypogenitalism, and profound mental retardation. We suggest that this is a new multiple congenital anomalies condition and mental retardation (MCA/MR) syndrome wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…In our review, which focused on patients with congenital facial weakness associated with impairment of ocular abduction [Verzijl et al, 2003], we observed that the familial cases usually presented with findings limited to the cranial nerves, and few additional features (such as the skeletal abnormalities), while sporadic cases showed other associated findings. Exceptions included the cases of Singh et al 1992, Criado and Perez Aytes 1999, and the present report. No specific skeletal abnormality could differentiate the sporadic patients, from the familial cases.…”
Section: To the Editormentioning
confidence: 54%
See 1 more Smart Citation
“…In our review, which focused on patients with congenital facial weakness associated with impairment of ocular abduction [Verzijl et al, 2003], we observed that the familial cases usually presented with findings limited to the cranial nerves, and few additional features (such as the skeletal abnormalities), while sporadic cases showed other associated findings. Exceptions included the cases of Singh et al 1992, Criado and Perez Aytes 1999, and the present report. No specific skeletal abnormality could differentiate the sporadic patients, from the familial cases.…”
Section: To the Editormentioning
confidence: 54%
“…Although there is not enough evidence to prove this mode of inheritance, it may be that in some instances the syndrome results from a new dominant mutation [Kumar, 1990]. Presumed autosomal recessive [Legum et al, 1981; Singh et al, 1992; Criado and Perez Aytes, 1999] and X‐linked recessive patterns of inheritance [Journel et al, 1989] have also been proposed, but they are less commonly reported. The description of Hanissian et al 1970, with monozygotic twins affected by Moebius syndrome, also suggests a possible genetic cause for the condition.…”
Section: To the Editormentioning
confidence: 99%
“…La afectación, generalmente, es bilateral, pero también existen casos de afectación unilateral que obligan a realizar el diagnóstico diferencial con la parálisis facial obstétrica, aunque la afectación de otros pares craneales y los hallazgos neurofisiológicos permiten diferenciar ambos procesos (70). Los estudios electrofisiológicos indican un proceso del tallo cerebral que afecta predominantemente los núcleos faciales y sus conexiones internucleares, en lugar de un sitio supranuclear o muscular de la participación (71).…”
Section: Electrodiagnósticounclassified
“…Familial patterns have also been identified but do not appear to contribute to a majority of cases [ 12 ]. Some have suggested that the presence or absence of limb anomalies may be an important indicator for decreased or increased risk of inheritance, respectively [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some have suggested that the presence or absence of limb anomalies may be an important indicator for decreased or increased risk of inheritance, respectively [ 3 ]. Various modes of inheritance have been identified across the literature of multiple subspecialties [ 12 15 ]. A specific and consistent genetic abnormality has not been clearly identified, though efforts continue and have shown some variation [ 16 22 ].…”
Section: Introductionmentioning
confidence: 99%